Prerequisites, International Context and Features of NATO’s Proxy War against Russia in Ukraine (2022–2023) - M. M. Shumilov; A. B. Gurkin (Управленческое консультирование, 2023)
The purpose of the article is to clarify the prerequisites, international context, and features of the armed conflict in Ukraine, which in the conditions of a Special Military Operation (SVO) has acquired the character of a protracted and exhausting proxy war between Russia and NATO countries. By now, Russian social scientists have generally developed an adequate understanding of the causes of the war and the goals of the warring parties. Their methodological position is clear and is mainly determined by political attitudes that have been repeatedly voiced by the President of the Russian Federation, the Head of the Russian Foreign Ministry, other senior officials, and representatives of interested departments. As a rule, this does not raise questions since the official Russian position is not actually imbued with ideology. At the same time, the publications of Western political scientists, experts, and journalists, especially those who adhere to the realistic paradigm, deserve attention. Their assessments and forecasts contribute to the formation of an objective picture of the Ukrainian crisis. During the study, it was found that the intentions of the NATO countries led by the United States, and, therefore, the background of their rivalry with Russia, have not changed during the SVO. They still expect to inflict a strategic defeat on our country and thereby prolong the existence of a unipolar world. Believing in Russia’s weakness, Western elites associate the end of the conflict with the victory of the Kiev regime on the battlefield. Therefore, the United States and its NATO allies continue to saturate Ukraine with more and more modern weapons. The main sponsor and organizer of the ongoing war is the United States, which pays two-thirds of Ukrainian military expenses. At the same time, their behavior is characterized by caution and even a certain responsibility. The United States fears an uncontrolled escalation of the conflict, every time it emphasizes its non-involvement in military actions and seeks to localize them within the borders of Ukraine. Even though the Russian Federation is also wary of striking at the territory of NATO countries, the conflict between them continues to develop in an escalating spiral. The war is gradually moving beyond the mediated relations between Russia and the countries of the North Atlantic Treaty Organization. With the expansion of supplies of increasingly destructive weapons and the direct involvement of NATO members in the confrontation with the Russian military, it acquires a full-fledged character with the prospect of going beyond the borders of Ukraine and using unconventional weapons.